Ultrafast B1 mapping with RF‐prepared 3D FLASH acquisition: Correcting the bias due to T1‐induced k‐space filtering effect - Zhu, Dan; Schär, Michael; Qin, Qin (Magnetic resonance in medicine, 2022)
Purpose The traditional radiofrequency (RF)‐prepared B1 mapping technique consists of one scan with an RF preparation module for flip angle‐encoding and a second scan without this module for normalizing. To reduce the T1‐induced k‐space filtering effect, this method is limited to 2D FLASH acquisition with a two‐parameter method. A novel 3D RF‐prepared three‐parameter method for ultrafast B1‐mapping is proposed to correct the T1‐induced quantification bias. Theory The point spread function analysis of FLASH shows that the prepared longitudinal magnetization before the FLASH acquisition and the image signal obeys a linear (not proportional) relationship. The intercept of the linear function causes the quantification bias and can be captured by a third saturated scan. Methods Using the 2D double‐angle method (DAM) as the reference, a 3D RF‐prepared three‐parameter protocol with 9 s duration was compared with the two‐parameter method, as well as the saturated DAM (SDAM) method, the dual refocusing echo acquisition mode (DREAM) method, and the actual flip‐angle imaging (AFI) method, for B1 mapping of brain, breast, and abdomen with different orientations and shim settings at 3T. Results The 3D RF‐prepared three‐parameter method with complex‐subtraction delivered consistently lower RMS error, error mean, error standard deviation, and higher concordance correlation coefficients values than the two‐parameter method, the three‐parameter method with magnitude‐subtraction, the multi‐slice DREAM and the 3D AFI, and were close to the results of 2D or multi‐slice SDAM. Conclusion The proposed ultrafast 3D RF‐prepared three‐parameter method with complex‐subtraction was demonstrated with high accuracy for B1 mapping of brain, breast, and abdomen.